2008
DOI: 10.1007/s00431-008-0897-5
|View full text |Cite
|
Sign up to set email alerts
|

Trampoline-related injuries in childhood

Abstract: Recommendations to prevent trampoline injuries were given since the 1970s. However, despite these educational efforts, safety recommendations seem to be ignored and the number of trampoline injuries is increasing. All children referred to our department for injuries related to trampolines over a period of 3 years were included. The patients' records were reviewed and a questionnaire was sent out in order to gain additional information. Injuries were classified as severe and mild. A total of 265 children (46% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 13 publications
(21 reference statements)
2
26
0
Order By: Relevance
“…A subsequent increase in trampoline injuries seen in emergency departments has caused some authors to recommend that trampolines should be banned [28][29][30] . However, reports on trampoline injuries have not considered exposure time or the possible positive effects of trampolines.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent increase in trampoline injuries seen in emergency departments has caused some authors to recommend that trampolines should be banned [28][29][30] . However, reports on trampoline injuries have not considered exposure time or the possible positive effects of trampolines.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing 2005 trampoline injury demographics and characteristics with those from 1990-1995 using the same data source, Linakis et al identified a steady increase in injuries each year over the period studied, noting that "physicians strongly encourage physical activity in children, and while trampolines appear to be a fun activity that satisfies the need for physical activity, this study indicates that they pose too great a threat to be used in an unsupervised environment like a back yard" (Mello, 2007). European researchers reported similar trends and Eberl et al (2009) concluded that "all attempts over a period of more than 30 years to reduce the number of trampoline-related backyard injuries failed, and the incidence is still increasing. At present, trampolines cannot be made safe for recreational activities and are of an unacceptable risk even under supervision" (p. 1171).…”
mentioning
confidence: 63%
“…Eberl et al (2009) reported that more than half of reported injuries occur on trampolines with safety nets. Nearly all injuries requiring medical attention occur on privately owned trampolines (Furnival et al, 1999;Leonard & Joffe, 2009;Linakis et al, 2007;Shields, Fernandez, & Smith, 2005).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Trampoline manufacturers often state in their product literature that only one person should use the apparatus at a time. Despite this, studies continue to report high instances of individuals hurt when there is more than one person on the trampoline, with rates quoted between 64% and 83% 11 12 14–18. Studies have also revealed that the lightest person is 5–14 times more likely to be injured when multiple people use a trampoline simultaneously 1 18.…”
Section: Introductionmentioning
confidence: 99%